Micro-evidence on rent sharing from different perspectives - Sabien Dobbelaere; Jacques Mairesse (Institute for the Study of Labor (IZA), 2010)
This article provides evidence of rent sharing from orthogonal directions by exploiting different dimensions in the same data. Taking advantage of a rich matched employer-employee dataset for France over the period 1984-2001, we consistently compare across-industry heterogeneity in rent-sharing parameters derived from three different approaches. The accounting approach and the standard labor economics approach are compatible with distinct labor bargaining settings (right-to-manage, efficient bargaining, labor hoarding) whereas the productivity approach hinges on the assumption of efficient bargaining. Across the different approaches, we evidently find differences in dispersion of the rent-sharing parameter estimates which could be attributable to differences in modeling assumptions and/or data requirements but these estimates lie within a comparable range. We interpret the latter finding as lending empirical support to efficient bargaining as the nature of the bargaining process in France over the considered period.
Keywords: C23; D21; J31; J51; 330; Rent sharing; wage equation; production function; matched employer-employee data; Lohnverhandlungen; Lohnstruktur; Produktionsfunktion; Panel; Frankreich